HOUSE “MACHINE À HABITER” FROM THE 21ST CENTURY - Luis Morei Luis Moreira Pinto; Paulo Carvalho; Susa Tavares dos Santos (European Scientific Journal, ESJ, 2014)
We intend, in this research paper, define how we think and how we see architecture. Today, there are several concepts about what interior space is; however, all sensory experiences confirm the way we see and interpret the space. This panoply of sensations and feelings is associated with an individual and specific mode of interpretation caused by the life experiences of the observer. It's like “walking” with eyes. According to Manfredo Tafuri, author of Theory and History of Architecture, the reality of architectural culture, including its incongruities and the daily increases in production, produces an unexpected result (Tafuri 1988, 00-44). This both dictates the death of architecture as well as the discovery of a new dimension and application of architecture in real life. In conclusion, we expect to achieve the objective of knowing what is meant by “home” in a generation where globalization is integral to the creative process, and to explore how this affects the process of “knowing” and “learning” how to undertake an architectural project. Today a house is a machine.